Mapping the Dynamics of European Elections: A Comparative Analysis of Voter Priorities, Campaign Strategies, and Electoral Outcomes (2019–2024) - Panagiotidou, Georgia; Bouranta, Vasiliki (International Conference on Business and Economics - Hellenic Open University, 2025)
Political marketing is a vital aspect of election campaigns, encompassing all facets of political behavior. Bigi (2017) emphasizes its role in providing frameworks for analyzing voter behavior and the positioning strategies of parties and candidates (Blumenthal, 1980; Nimmo, 1999; Sparrow & Turner, 2001). The "4 Ps" marketing mix—product, price, place, and promotion—is central to political campaigns. Here, the “product” includes the party, candidates, image, and the agenda (Farrell & Wortmann, 1987; Shaw, 1994). “Price” is not monetary but rather the ideological, emotional, and policy trade-offs voters must consider before making an electoral choice. “Place” relates to party organization, and “promotion” covers communication strategies (Bigi, 2017).This study conducts an in-depth, comparative analysis of the 2024 European elections, both cross nationally and in relation to the 2019 elections, not only by examining electoral outcomes but also by exploring the role of issue-based voting and the strategic use of political marketing. Data from across 27 EU member states was gathered on party positioning along four axes: 'Left-Right,' 'Liberalism Authoritarianism,' 'European Cooperation-National Isolation,' and 'Modernization Conservatism.' The analysis also included media usage, television, radio, internet, and social media, and issues highlighted in campaign agendas. Using multivariate quantitative methods, the study identifies typologies of European parties based on competition axes, media use, and agendas, highlighting parties' political behavior in national and European contexts, uncovering convergences and divergences in strategies. Finally, the research examines how agenda-setting and political product positioning influence electoral strategies, offering insights into the evolving dynamics of political marketing in the EU. JEL Classifications: C38, D72, M31 Keywords: Political marketing; Political competition; Election campaign; European elections; Comparative politics; Voting behavior